60 GHz channel characterisation and key performance evaluation of HD video transmission. Issue 12 (1st September 2016) - Leonor, Nuno R.; Caldeirinha, Rafael F.S.; Fernandes, Telmo R.; Gaddam, Nagavenkat K.
Abstract : This study presents a practical assessment of the recent IEEE 802.15.3c statistical model aimed at the characterisation of 60 GHz indoor radio channels, for high‐definition (HD) video streaming, envisaging tele‐health applications. A simple ray‐tracing model was developed to characterise the 60 GHz propagation channel and to compare it with the recent IEEE standard, in an indoor scenario mimicking a surgical room. Additionally, a measurement campaign was carried out to validate those model approaches and subsequently analyse the propagation path loss and time dispersion parameters of the propagation channel in the typical usage scenarios. Finally, the severity of multipath effects on the key performance indicators of HD video transmission, under line‐of‐sight (LOS) and non‐LOS situations, were evaluated.